Isolated flavonoids from Ficus racemosa stem bark possess antidiabetic, hypolipidemic and protective effects in albino Wistar rats. (2nd April 2016) - Keshari, Amit K.; Kumar, Ghanendra; Kushwaha, Priya S.; Bhardwaj, Monika; Kumar, Pranesh; Rawat, Atul; Kumar, Dinesh; Prakash, Anand; Ghosh, Balaram; Saha, Sudipta
Abstract: Ethnopharmacological relevance: Ficus racemosa (FR) has been used for thousands of years in Ayurvedic system of medicine in India and is closely associated with prevention, treatment and cure of various human ailments like obesity and diabetes. It is popularly known as gular. A vast and wide range of chemical compounds like polyphenols, friedelane-type triterpenes, norfriedelane type triterpene, eudesmane-type sesquiterpene including various glycosides had been isolated from this plant. However, no detail studies related to isolation of flavonoids has been reported previously with their antidiabetic, hypolipidemic and toxicological consequences. Aim of the study: The present study was undertaken to evaluate antidiabetic, hypolipidemic and toxicological assessments of flavonoids isolated from Ficus racemosa (FR) stem bark. Materials and methods: We isolated four flavonoids from stem bark of FR and structures were confirmed by Infrared spectroscopy (IR), Nuclear Magnetic Resonance (NMR) (both 1D and 2D), mass spectroscopy (MS). Later, these flavonoids were administered to streptozotocin (STZ) rats once in a day for a period of seven days at 100 mg/kg dose. We measured blood glucose level and body weight changes at different days (1st, 3rd, 5th and 7th days). Serum lipid profiles were also estimated to investigate the hypolipidemic potential of flavonoids in the similar experiment. Various oxidative stress parameters in pancreas and liver and hepatic biomarker enzymes in plasma were also determined to investigate the toxicity potential of isolated flavonoids. Finally, we performed docking studies to find out the mechanism of action. Results: Our results collectively suggested that four flavonoids reduced blood glucose level and restored body weight, signifying antidiabetic action. There were reduction of other lipid profile parameters and increase of high density lipoprotein (HDL) during administration of flavonoids, also signifying hypolipidemic action. Various oxidative stress biomarkers and hepatic enzymes levels were also normalized with respect to diabetic control at the same time. Docking studies revealed that isolated flavonoids showed their antidiabetic potential via binding to PPARγ and GLUT1 receptors. Conclusion: The isolated four flavonoids demonstrated good antidiabetic, hypolipidemic and antioxidant properties in STZ diabetic rats which supported the use of FR stem bark as useful supplementary drug for future antidiabetic therapy. Graphical abstract: Highlights: Isolation and Structure confirmation through FTIR, NMR (1D and 2D) and MS. Antidiabetic and hypolipidemic activities using streptozotocin induced albino Wistar rats. Toxicological assessments in liver and pancreas. Mechanistic study to PPARγ and GLUT1 receptors through molecular docking.